Recognition of Speech of Normal-hearing Individuals with Tinnitus and Hyperacusis - Hennig, Tais Regina; Costa, Maristela Julio; Urnau, Daila; Becker, Karine Thaís; Schuster, Larissa Cristina (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: Tinnitus and hyperacusis are increasingly frequent audiological symptoms that may occur in the absence of the hearing involvement, but it does not offer a lower impact or bothering to the affected individuals. The Medial Olivocochlear System helps in the speech recognition in noise and may be connected to the presence of tinnitus and hyperacusis.Objective: To evaluate the speech recognition of normal-hearing individual with and without complaints of tinnitus and hyperacusis, and to compare their results.Method: Descriptive, prospective and cross-study in which 19 normal-hearing individuals were evaluated with complaint of tinnitus and hyperacusis of the Study Group (SG), and 23 normal-hearing individuals without audiological complaints of the Control Group (CG). The individuals of both groups were submitted to the test List of Sentences in Portuguese, prepared by Costa (1998) to determine the Sentences Recognition Threshold in Silence (LRSS) and the signal to noise ratio (S/N). The SG also answered the Tinnitus Handicap Inventory for tinnitus analysis, and to characterize hyperacusis the discomfort thresholds were set.Results: The CG and SG presented with average LRSS and S/N ratio of 7.34 dB NA and −6.77 dB, and of 7.20 dB NA and −4.89 dB, respectively.Conclusion: The normal-hearing individuals with or without audiological complaints of tinnitus and hyperacusis had a similar performance in the speech recognition in silence, which was not the case when evaluated in the presence of competitive noise, since the SG had a lower performance in this communication scenario, with a statistically significant difference.
Keywords: audiology; hyperacusis; speech perception; speech discrimination tests; tinnitus